Pengaruh Pemberian Metode Bermain Untuk Meningkatkan Perilaku Asertif Anak - Aliyati, Azmi Nur (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
AbstrakThe purpose of this research is to understand implementation of role play method to affect children assertive act. In this research we use TK ABA Kanggotan Pleret class A.1 as the group subject experiment and class A.2 as the group subject control in the school year 2012/2013. The research scheme usingÂ pre post test control group design, data collecting method using child behavioral checklist (CBCL), and the analyzing method using statistics non parametric with mann whitney test as the comparison with dual samples independent and wilcoxon test as the comparison with dual samples dependent. From mann whitney test the result is p=0,003 (p<0,05) and from wilcoxon test the result is 0,012 (p<0,05) for experiment group, meanwhile the result for control group is p=0,066 (p<0,05). From the data analyze we can conclude that role play method effective to improve the children assertive act. So that, the hypothesis in this reaserch, which is that role play method is effective to affect the children assertive act can be accepted.Keywords : play, role play, assertive behavior.